Ireland : Financial Sector Assessment Program: Technical Note-Insurance Sector and Update on the Assessment of Observance of the Insurance Core Principles. (IMF Staff Country Reports; Country Report, 2016)
This Technical Note discusses the findings and recommendations made in the Financial Sector Assessment Program for Ireland's insurance sector. Insurance in Ireland is well developed, diverse, and has a large international business presence. Insurance penetration in Ireland is almost three times the EU average. Many recommendations have been implemented by the central bank, with Solvency II now the solvency regime in Ireland. In total, 51 Supervisory Review Process guidance papers have been prepared setting out the central bank's internal supervisory processes and procedures under Solvency II with reference to the technical standards and guidelines and the central bank's prioritization framework. Forty-seven of these were complete as of the end of 2015.